ปัจจัยเชิงเหตุแบบบูรณาการทางด้านจิตลักษณะและสถานการณ์ ที่เกี่ยวข้องกับพฤติกรรมการบริการบนเครื่องบินของพนักงานต้อนรับบนเครื่องบิน - ศุภสมุทร(Dinh Supasamut), ดิณห์; พันธุมนาวิน(Duchduen Bhanthumnavin), ดุจเดือน (Journal of Behavioral Science for Development, 2016)
(Integration of Psychological and Situational Antecedents of In-flight Service Behavior in Cabin Crew) Abstract This correlational study aimed at investigating the important predictor of the situational and psychological factors on in-flight service behavior. The sample of 411 cabin crew consisted of 165 males (40.1%) and 246 females (59.9%), with the average age of 39.10 years. It was obtained by the technique of Multi-stage Sampling from Thai Airways International Public Company Limited. Multiple regression analysis results revealed that the situational factor, the psychological trait and the psychological state can be operated for prediction on in-flight service behavior 42.50%. The predictor found that the need for achievement was the highest level and in addition, the researcher found the at-risk group such as male cabin crew, reginal/domestic route cabin crew and young cabin crew. In order to enhance in-flight service behavior, the following factors need to be increased. They are need for achievement, future orientation and low work stress. These results have important implications for further research and promoting interventions. Keywords: integration of psychological and situational, in-flight Service behavior, cabin crew, Multiple Regression Analysis, Three-way Analysis of Variance